Factors Affecting Public Acceptance of the Covid-19 Vaccine in Indonesia - Anggraheny, Hema Dewi; Lahdji, Aisyah (South East Asia Nursing Research, 2022)
One of the efforts to protect the community against Covid-19 cases is vaccination. However, in the preparation of vaccination, there are several negative issues related to vaccines, which make people doubt and even reject the effort. Predisposing factors include age, gender, occupation, income, education level, history of contact with people with COVID, and knowledge of vaccines, which can affect acceptance of vaccines. The purpose of this activity is to find out what factors affect public acceptance of the Covid-19 vaccine. The research was conducted by distributing questionnaires via google form to the general public in January 2021. The total respondents were 411 respondents. The questionnaire uses the Public Perception Survey questionnaire for the Covid-19 Vaccine in Indonesia published by WHO and the Ministry of Health of the Republic of Indonesia. Analysis using Chi-Square test. The survey results showed that 46.2% of respondents had not decided on and refused the vaccine, and 94.2% wanted to get information about the vaccine. Factors related to vaccine acceptance include age, work in the health sector, income level, education, fear of vaccines, the thought that there are many hoaxes regarding the COVID-19 vaccine, thoughts on vaccine safety, and thoughts on the dangers of vaccines. Accurate and scientific information, accompanied by easy access to receive the Covid-19 vaccine, is needed so that people with self-awareness carry out vaccinations to reduce the morbidity and mortality of COVID-19 in Indonesia.